Effectiveness of PBL with Environmental Literacy and Local Wisdom on Elementary Learning Outcomes - Ninin Harjiyanti; Joko Siswanto; Joko Sulianto (Journal of Educational Studies, 2026)
This study aims to analyze the effectiveness of Problem-Based Learning (PBL) integrated with environmental literacy and local wisdom in enhancing the learning outcomes of third-grade elementary school students. The research method employed is a quantitative approach with a comparative study design. The population of this study consists of all third-grade students at SDN Candi and SDN Batiombo 02, with a sample of 46 students. This sample includes 25 students in the experimental class implementing PBL integrated with environmental literacy and 21 students in the control class implementing PBL integrated with local wisdom. Data collection techniques included tests (pre-test and post-test), as well as teacher and student observation sheets. Data analysis was conducted using descriptive analysis, normality tests, homogeneity tests, hypothesis testing with paired sample t-tests, and N-Gain tests. The results of the study indicate a significant improvement in learning outcomes in both classes, with a significance value of 0.000 (< 0.05). The N-Gain test results show that the experimental class achieved an average score of 0.7129 (high category), while the control class achieved 0.6096 (moderate category). Furthermore, teacher and student activities in the experimental class were more optimal than those in the control class. The findings of this study demonstrate that the Problem-Based Learning (PBL) model integrated with environmental literacy is more effective than the Problem-Based Learning (PBL) model integrated with local wisdom in improving the learning outcomes of third-grade elementary school students.